Authoritarian Leadership and Distributive Justice as a Determinant of Employee Job Satisfaction: A Case Study in Idi Tunong, East Aceh - Jasmadi, Jasmadi; Silalahi, Valen Parningotan; Norman, Yenny; Ompusunggu, Rudolf Yamasoni; Restianan, Rizni; Helmi, Tengku Ahmad (Economics, Business and Management Science Journal, 2025)
This study aims to analyze the influence of authoritarian leadership and distributive justice on employee job satisfaction in Idi Tunong, East Aceh. Using a quantitative approach with a survey method, data was collected through a questionnaire filled out by 46 employees. Data analysis was carried out with descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that authoritarian leadership had a significant negative influence on job satisfaction (r = -0.42), while distributive justice had a significant positive influence (r = 0.61). Regression analysis shows that distributive justice plays a greater role in increasing job satisfaction than the negative influence of authoritarian leadership. These findings support the theory of leadership and distributive justice, where an overly authoritarian leadership style can reduce employee motivation and satisfaction, but the application of good fairness principles can improve employee welfare and organizational productivity. In conclusion, leaders in the public sector need to reduce authoritarian approaches and improve distributive justice to maintain employee job satisfaction